Microclonal propagation in vitro of commercial varieties of rose (Experimental biology, 2018)
To propagate the seedling of hybrid and commercial varieties roses of Kazakhstan breeding, adapted to the arid regions of Western Kazakhstan, the microclonal propagation in vitro technology was used. For introduce hybrid roses in in vitro culture, the nodal segments with axillary buds, as well as the internode segments taken from plants actively growing in Mangishlak experimental botanic garden, were isolated in aseptic conditions. Sterilization by treating the explants with a 10% solution of hydrogen peroxide for 8 minutes was the most effective, than its treatment by 70% ethanol (20 sec.) and subsequent 5-minute exposure in 5% sodium hypochlorite. Due to this method of disinfection, the yield of viable explants was maximal - 68.4%. Cloning of roses was carried out on different variants of Murashige-Skug medium modified by phytohormones. The greatest number of microclones was obtained on MS medium containing 3 mg/l BAP and 0.5 mg/l NAA. Ascorbic acid (0.5 mg/l) was added into MC medium as an antioxidant. For rooting was used MC medium with 2 mg/l IAA. The multiplication rate in this case was 4. This optimized protocol is recommended for the introduction of commercial varieties of roses, as well as for gardening of the Caspian region.